The Influence of The Variable Pressure of Oscillation Wave on The Conductivity Properties of Porous Media - Bekjonov Rozisher Soatmurodovich (Scientific Trends, 2023)
Khovdak oil field is located in Sutkhandarya region of the territory Zharkhurgan district. . The mine is located 55 km north-west of the city of Termiz and 18 km north-west of the city of Zharkurgan. . The connection of transport of the mine with the cities of Zharkurgan and Termiz is carried out by roads and railways passing through the center of the Surkhan oasis. In 1931, N. P. Toraev determined the mining uplift structure in the Khovdak field with the help of geological imaging. In 1932, based on his recommendation, it was planned to drill an exploration well in the part of the mine dome. Exploration well No. 1 was placed in the southern part of the southern elevation of the field, and in February 1934, during drilling, when the depth reached 158 m, an oil well was obtained from the I-horizon of the Bukhara layer of the Paleogene period, 140 tons of oil were produced per day.